2009
DOI: 10.1016/s9999-9994(09)20447-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Architecture and the Generation of Antigen Receptor Diversity

Abstract: The adaptive immune system generates a specific response to a vast spectrum of antigens. This remarkable property is achieved by lymphocytes that each express single and unique antigen receptors. During lymphocyte development, antigen receptor coding elements are assembled from widely dispersed gene segments. The assembly of antigen receptors is controlled at multiple levels, including epigenetic marking, nuclear location, and chromatin topology. Here we review recently uncovered mechanisms that underpin long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 49 publications
(66 reference statements)
0
54
0
Order By: Relevance
“…Conformational changes of antigen receptor loci are believed to support V(D)J recombination events because they can bring distant RSSs into proximity and therefore increase the probability of RSS synapsis (2,3). Studies using 3D-FISH have demonstrated that lineage-and development stage-specific locus contraction marks the recombination windows at antigen receptor loci (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conformational changes of antigen receptor loci are believed to support V(D)J recombination events because they can bring distant RSSs into proximity and therefore increase the probability of RSS synapsis (2,3). Studies using 3D-FISH have demonstrated that lineage-and development stage-specific locus contraction marks the recombination windows at antigen receptor loci (3).…”
mentioning
confidence: 99%
“…Studies using 3D-FISH have demonstrated that lineage-and development stage-specific locus contraction marks the recombination windows at antigen receptor loci (3). For example, the 3-Mb Igh locus contracts specifically in pro-B cells to support V H -to-D H J H recombination (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…When Igh is accessible to the recombination machinery, chromosomal contraction and DNA looping enable recombination, whereas chromosomal expansion inhibits the recombination (46,47). During VDJ recombination of Igh, the chromatin of the locus is organized in compartments containing clusters of loops separated by linkers, and the entire repertoire of V regions merges and juxtaposes to D elements (48,49). Productive V-DJ recombination at the Igh locus leads to reversal of locus compaction, and this decontraction was postulated to enforce allelic exclusion (47).…”
Section: Discussionmentioning
confidence: 99%
“…The developmental and locus-specific constraints on V(D)J recombination are largely imposed at the epigenetic level (Jhunjhunwala et al 2009). In nonlymphoid cells, the Ig and TCR genes are present in inaccessible chromatin because exogenously expressed RAG proteins readily cleave transfected episomal recombination substrates but not endogenous antigen receptor genes in kidney cells (Romanow et al 2000).…”
Section: Developmental Regulation Of Antigen Receptor Gene Rearrangemmentioning
confidence: 99%